Ambulance use, distance and outcomes in patients with suspected cardiovascular disease: a registry-based geographic information system study. Issue 1 (1st March 2020) - Sepehrvand, Nariman; Alemayehu, Wendimagegn; Kaul, Padma; Pelletier, Rick; Bello, Aminu K; Welsh, Robert C; Armstrong, Paul W; Ezekowitz, Justin A
Abstract: Background: Despite guideline recommendations, the majority of patients with symptoms suggestive of acute coronary syndrome do not use emergency medical services to reach the emergency department (ED). The aim of this study was to investigate the factors associated with EMS utilisation and subsequent patient outcomes. Methods: Using administrative data, all patients who presented to an ED in the metropolitan areas of Edmonton and Calgary in the years of 2007–2013 with main ED diagnosis of acute coronary syndrome, stable angina or chest pain were included. The travel distance was estimated using the geographic information system method to approximate the distance between the ED and patient home. The clinical endpoints were the 7-day and 30-day all-cause events (death, re-hospitalisation and repeat ED visit). Results: Of 50, 881 patients, 30.5% presented by emergency medical services. Patients with older age, female sex, ED diagnosis of acute coronary syndrome, more comorbidities and lower household income were more likely to use emergency medical services to reach the hospital. Longer travel distance was associated with higher emergency medical services use (odds ratio 1.09, 95% confidence interval 1.09–1.10), but it was not a predictor of clinical events. After adjustment for covariates and inverse propensity score weighting, emergency medical services use was associated with a higher risk of 7-day and 30-day clinical events. Conclusion: Several demographic and clinical features were associated with higher emergency medical services use including geographical variation. Although longer travel distance was shown to be linked to higher emergency medical services use, it was not an independent predictor of patient outcome. This has implications for the design of emergency medical services systems, triage and early diagnosis and treatment options.